PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP PRESTASI KERJA PT. MULTI PRATAMA INTERBUANA INDONESIA - Irwan Indriyanto (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2021)
To determine the effect of competence and motivation on work performance. This research is to analyze the causal relationship between competence and motivation on job performance. The data used are primary data by distributing questionnaires to employees of PT. Multi Pratama Interbuana Indonesia. The analysis method uses descriptive analysis and partially or simultaneous linear regression analysis. The sample used was 59 employees from a total population of 142 employees who were obtained using Slovin with a 10% annoyance level. The results showed that both partially and simultaneous there was a positive and significant influence on competence and motivation on employee performance.